Recent Patterns of Stunting and Wasting in Venezuelan Children: Programming Implications for a Protracted Crisis - Raffalli, Susana; Villalobos, Carlos (Frontiers in Sustainable Food Systems, 2021)
This study aims to assess the wasting and stunting patterns and their concurrence among vulnerable Venezuelan children. We performed an analysis of 46,462 anthropometric records captured by Caritas Venezuela between 2017 and 2019 of children under 5 years old in the poorest parishes. Based on the WHO 2006 child growth standards, we identify 31.7% and 11.5% of the records from 2019 as stunted and wasted, respectively. Our unconditional analysis shows that stunting was more frequent among boys and shows an inverted U-shape association with age. The prevalence of stunting increases from 0.28 in 2017 to 0.32 in 2019. By contrast, the wasting prevalence decreases from 0.15 in 2017 to 0.11 in 2019. The simultaneous concurrence of stunting and wasting slightly decreases over the same period from 0.045 to 0.039, all three trends being statistically significant. Using multilevel regression models, our conditional analysis shows that the odds of wasted children being stunted are 1.079 times greater than for non-wasted children. Similarly, the odds of stunted children being wasted are 1.085 times greater than for non-stunted children. While age is not statistically associated with stunting, it reduces the likelihood of being wasted. Furthermore, each additional month of age reduces by 1.16% the odds of facing the simultaneous concurrence of stunting and wasting instead of not facing it. The children’s sex is also found to have a significant association with the probability of stunting and wasting. The odds of stunting and wasting amongst boys are found to be 1.19 and 1.084 times greater than for girls, respectively. We also found a significant and sizeable association between food insecurity and both stunting and wasting. Although lack of access to clean water is not associated with stunting, it is associated with higher levels of wasting. Protracted humanitarian crisis in Venezuela has brought considerable damage to child growth. Findings have policy and programming implications: stunting should be targeted as a humanitarian priority in protracted crisis, not only to mitigate the growth failure in children facing multiple nutritional deficiencies, but also as an approach for preventing persistent acute malnutrition.